Hydrocolloids as binders for graphite anodes of lithium-ion batteries. (10th February 2015) - Cuesta, Nuria; Ramos, Alberto; Cameán, Ignacio; Antuña, Cristina; García, Ana B.
Graphical abstract: Highlights: Seven water-soluble hydrocolloids are tested as binders for graphite anodes in LIBs. All hydrocolloids meet the thermal and electrochemical stability required. Optimal binder concentration of 5 wt% is found for graphite/hydrocolloid electrodes. Four of them show cycling performances comparable to graphite/PVDF electrode. ABSTRACT: A series of seven different hydrocolloids are tested as water-soluble binders for synthetic graphite (SG)-based electrodes of lithium-ion batteries (LIBs) and compared with the standard poly(vinylidene difluoride) (PVDF) binder. The hydrocolloids selected are sodium carboxymethyl cellulose (Na-CMC), sodium alginate (Na-Alg), gum arabic (GA), xanthan gum (XG), guar gam (GG), agar-agar (AA) and carrageenan (CAR), the latter three with no precedents in the literature. They all show thermal and electrochemical stability under the experimental conditions employed. For SG/hydrocolloid electrodes, binder concentrations of 5 wt% are found to be optimal, providing outstanding electrochemical performances for electrodes with Na-Alg Na-CMC, XG and GG in galvanostatic cycling experiments at constant (C/10, with C = 372 mA g −1 ) and variable (from C/10 to 2C) current rates, which are comparable, or even superior to those of SG/PVDF electrodes with higher binder content (8 wt%). In contrast, SG/GA, SG/CAR and SG/AA electrodes show poorer electrochemical performances, most likely owing to the low adhesion capacity of the binder (GA and CAR), or the formation of films covering the SG particles (CAR and AA).